(untitled) (Bangladesh Critical Care Journal, 2021)
COVID-19 has proved to cause multi-systemic manifestations in many reported cases across the world. Here, we report a rare presentation of a 20 years old COVID-19 positive male patient with acute kidney injury who developed ophthalmoplegia during the course of the disease. COVID-19 being a relatively new disease, its neurological manifestation is even rarer with limited literature concerning the symptoms. Clinicians should, therefore, have a high suspicion and awareness regarding the many faces of the severe acute respiratory syndrome coronavirus-2(SARS-CoV-2), for early detection and mitigation of the disease, especially during the pandemic. Bangladesh Crit Care J March 2021; 9(1): 59-61